Gastrointestinal parasites in dogs 6 months old or younger sold in 18 pet stores in the great metropolitan area of Costa Rica. - Calderón, S. (2012)
The aim of this study was to identify the gastrointestinal parasites (GIP) in dogs younger than 6 months old,sold in 18 pet stores in the great metropolitan area of Costa Rica. All facilities surveyed had regent veterinarian.Spanning a four months period, faecal samples were collected from 184 dogs, which were analyzed by direct mi-croscopy (saline / iodine) and Sheather flotation (a hypersaturated sugar solution, density 1.3). Of the 184 sam-ples, 100 (54.3%) had the following gastrointestinal parasites (GIP) Coccidia (27.7%), Ancylostomatids (19.0%),Toxocara canis (18.5%), Giardia sp. (10.3%) and Dipylidium caninum (0.5%). Among these, only Coccidia nothave zoonotic potential. Were identified 10 deworming protocols, and the percentages of positive animals GIPusing these protocols ranged from 37.2% to 77.7%. Control of the GIP in these stores is based solely on theuse of anthelmintics, without a parasitological analysis. The percentage of infected animals and the repertoirediagnosed were not expected, since according to the regents or owners, the animals were dewormed at the timeof admission. Detection of GIP with zoonotic potential in dogs younger than 6 months old, sold under the “assu-rance that they are free of parasites”, highlights the role of the regent veterinarian for the veterinary public health.The results also underscore the importance of continuing education for the veterinarians of canines and felinesin the country, with emphasis on appropriate diagnosis and control practices of GIP.